صياغة أسئلة البحث للبحوث العلمية في تعليم اللغة العربية - Arief Rahman Hakim (Universitas Islam Negeri Palangka Raya, 2016)
Research problem is the first thing to be found by researcher. Then, he should limit it clearly so that it can be easy to be understood. At this step, the researcher needs special formula to write the problems statement in the form of research questions which the answers of them are the research goals.